Manusia Penata Alam dan Bukan Penakluk Alam - Manggala Kala’tasik, Veronika Restu (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
Man was created with the mandate or responsibility to nurture another creation. The creation of the others in this regard is no exception to nature. Nature by not merely being created by the Creator but, through the realm of man, the glory of God is revealed. Man who is a noble creation is given the trust to keep nature and continue to declare the glory of God. Man must take good care of, maintain, work on nature. Man's covetousness of the beauty and richness of nature makes man "forget" the mandate that the Creator entrusts. The universe is also a creation that has value for that man as a noble creation should have the consciousness to maintain that value (as a sesame of creation). The methodology used is a descriptive analysis study. The reference sources used are literacy references such as related books and journals. This writing intends to open up the mindset and give awareness of the importance of maintaining or being a stylist not a conqueror of nature. Qualitative methods are used through literature studies in this writing. The increasing needs of man seem to force to make desires a necessity that leads to the destruction of nature. For this reason, it is necessary to be aware and live enough and be grateful.ABSTRAKManusia diciptakan dengan mandat atau tanggungjawab untuk memelihara ciptaan yang lain. Ciptaan yang lain dalam hal ini tidak terkecuali alam. Alam dengan tidak hanya sekedar diciptakan oleh Sang pencipta begitu saja namun, melalui alam manusia kemuliaan Tuhan dinyatakan. Manusia yang adalah ciptaan yang mulia diberikan kepercayaan untuk menjaga agar alam tetap dan terus menyatakan kemuliaan Tuhan. Manusia harus menjaga, memelihara, mengusahakan alam dengan baik. Ketamakan manusia akan keindahan dan kekayaan alam membuat manusia “lupa” akan mandat yang Sang Pencipta percayakan. Alam semesta pun merupakan ciptaan yang mempunyai nilai untuk itu manusia sebagai ciptaan yang mulia seharusnya memiliki kesadaran untuk menjaga nilai tersebut (sebagai sesame ciptaan). Adapun metodologi yang digunakan adalah studi deskriptif analisis. Sumber rujukan yang digunakan adalah referensi literasi seperti buku dan jurnal terkait. Penulisan ini bermaksud untuk membuka pola pikir serta memberi kesadaran akan pentingya menjaga atau menjadi penata bukan penakluk alam. Digunakan metode kualitatif melalui studi pustaka dalam penulisan ini. Kebutuhan manusia yang semakin meningkat seolah-olah memaksa untuk menjadikan keinginan sebagai kebutuhan yang berujung pada pengrusakan alam. Untuk itu, diperlukan kesadaran serta hidup cukup dan bersyukur.